Adobe Creative Suite 6 Design and Web Premium All-in-One for Dummies - Smith, Jennifer ; Smith, Christopher, 1969- and Gerantabee, Fred (Hoboken, New Jersey John Wiley & Sons, 2012)
The must-have book on the leading suite of software for graphic and web designersFully revised and updated this hands-on resource offers a one-stop learning opportunity through eight mini-book dedicated to each product inside Adobe's Design ; Web Premium Suite. The mini-books include Adobe Creative Suite Basics, InDesign, Illustrator, Photoshop, Acrobat, Dreamweaver, Flash, Fireworks. The book may contain new image enhancements to After Effects, 64-bit versions of Illustrator and Flash Professional, and a new tool, dubbed Helium, that will enable designers to create content using HTML5 and CSS3. Contains new and updated content that will reflect the latest updates to softwareOffers the depth needed by novices and long-time professionalsCovers the key features and tools users need to master individual programs to their fullest capacitiesHelps designers to be more creative and productiveFilled with tips and techniques for using the 8 design programsThis popular package gives designers a full review of the most popular design and development tools on the market.
Include Illustration and Index
Keywords: Web sites--Authoring programs -- Computer graphics -- Desktop publishing